Re-sequencing and morphological data revealed the genetics of stone shell and kernel traits in apricot - Zhang, Qiuping; Zhang, Yuping; Liu, Weisheng; Liu, Ning; Ma, Xiaoxue; Lü, Chunjing; Xu, Ming; Liu, Shuo; Zhang, Yujun (Frontiers in Plant Science, 2023)
The kernel-using apricot (Prunus armeniaca L.) is an economically important fruit tree species in arid areas of because of its hardiness and cold and drought tolerance. However, little is known about the genetic background and trait inheritances. In the present study, we firstly evaluated the population structure of 339 apricot accessions and the genetic diversity of kernel-using apricot using whole genome re-sequencing. Secondly, the phenotypic data of the 222 accessions was investigated for two consecutive seasons (in 2019 and 2020) for nineteen traits, including kernel and stone shell traits, and pistil abortion rate of flowers. The heritability and correlation coefficient of traits also were estimated. Length of stone shell (94.46%) showed the highest heritability, followed by the length/width ratio (92.01%) and length/thickness ratio (92.00%) of stone shell, being very low for the breaking force of nut (17.08%). Then, a genome-wide association study (GWAS) revealed a total of 120 quantitative trait loci (QTLs) using general linear model (GLM) and generalized linear mixed model (LGMM). The QTLs of kernel and stone shell traits were unevenly assigned on the eight chromosomes. Out of 1272 candidate genes identified in the eleven consistently reliable QTLs found using two GWAS methods and/or at two seasons, 781 were annotated. Interestingly, the sweet kernel (SK) trait was assigned to chromosome 5 of genome as well as the almond, and a new locus was also mapped on the 17.34-17.51 Mb on the chromosome 3, including 20 candidate genes. Those loci and genes identified here will be of significant use in molecular breeding efforts, and the candidate genes will play essential roles in exploring the mechanisms of genetic regulation.